Politics as Art: The Creation of a Successful Political Brand - Kravchenko, Nataliia К.; Goltsova, Marianna Gennadiivna; Kryknitska, Iryna O. (Journal of History Culture and Art Research, 2020)
The article identifies the functions of the archetypal semiotic resource, based on archetypal plots, situations, characters, and symbols, in political discourse signification and mythologization. The value framework of the discourse of the Ukrainian party “Servant of the People” was laid down by the similarly-named TV series narrative, involving archetypal patterns, consonant with the values and needs of TV viewers. The stages in the formation of the main character are associated with the Hero’s journey in Joseph Campbell’s Monomyth: the search for yourself; the "initiation" experienced both oneirically and in firm reality, in a form of imprisonment; and the "return" in a renewing capacity. Plotlines-associated archetypes encompass a battle of Good and Evil, the transformation from Rags to Riches, and the theme of the Hero’s Task related to a monomyth’s circular principle. The image of the protagonist incorporates a set of archetypal characters of the Hero, Caregiver, Innocent, Rebel or Destroyer, Ruler, Seeker, Creator, Sage, Everyman, and Jester, consonant with the individual viewer’s emotional and cognitive structures. Due to their correlation with basic human values, these archetypal patterns facilitate the development of a secondary level of signification or mythologization – that of discourse-forming values. These core discourse values are most closely related to the Caregiver archetype, ambivalently embodying either the need for belonging, concern, and assistance, as well as a confirmation of one’s own sense of worth. The multimodal social semiotic analysis shows a certain rearticulation of the party’s discourse values. Their main values are still associated with the Caregiver archetype, embodied in the party name itself, “Servant of the people”, as these values unite different people into the widest possible “inner group”. However, today the core functions in the construction of party discourse belong to the values associated with the Creator archetype, addressing the highest level in the hierarchy of needs – that of Self-Actualization.